2016
DOI: 10.1007/s00253-015-7251-4
|View full text |Cite
|
Sign up to set email alerts
|

TAT-HSA-α-MSH fusion protein with extended half-life inhibits tumor necrosis factor-α in brain inflammation of mice

Abstract: Neuroinflammation constitutes a principal process involved in the progression of various central nervous system (CNS) disorders, including Parkinson's disease, Alzheimer's disease, ischemic stroke, and traumatic brain injury. The safety and efficacy of potential neuroprotective therapeutic agents is controversial and limited. Alpha-melanocyte-stimulating hormone (α-MSH) as a tridecapeptide derived from pro-opiomelanocortin displays potent anti-inflammatory and protective effects with a wide therapeutic window … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…The half-life for TAT-conjugated peptides is cargo-dependent and has been found to range from 1 h to as high as 18 h (Krosl et al, 2003;Bach et al, 2012;Wang et al, 2016). Our two-photon data indicated that the FitC-tagged TAT-C1aB remained detectable above baseline in the CNS vasculature for Ն2 h after intraperitoneal injection (Fig.…”
Section: Tat-c1ab Provides Neuroprotection In Vivomentioning
confidence: 57%
“…The half-life for TAT-conjugated peptides is cargo-dependent and has been found to range from 1 h to as high as 18 h (Krosl et al, 2003;Bach et al, 2012;Wang et al, 2016). Our two-photon data indicated that the FitC-tagged TAT-C1aB remained detectable above baseline in the CNS vasculature for Ն2 h after intraperitoneal injection (Fig.…”
Section: Tat-c1ab Provides Neuroprotection In Vivomentioning
confidence: 57%
“…αMSH as a tridecapeptide derived from POMC displays potent anti-inflammatory role in many tissues and has protective effects on therapies in brain damage, liver or lung fibrosis, skin inflammation and chronic adipose inflammation. The fusion protein TAT-HSA-α-MSH inhibits NF-κB activation in human and TNFα production in mice to prevent brain inflammation in central nervous system (CNS) disorders [ 34 , 35 ]. αMSH has also been confirmed to inhibit antigen-induced allergic skin inflammation, abolish monocytes adhesion to vascular endothelium, attenuate bleomycin-induced pulmonary inflammation, blunt adipose oxidative stress and inflammation, and protect from adipose tissue apoptosis and fat deposition [ 24 , 36 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of a DS cell adhesion molecule has important consequences in neuronal proliferation, maturation, and synaptogenesis that appear to be mediated via a Pak-dependent pathway activating LIMK and inactivating cofilin (Perez-Nunez et al, 2016). Another chromosome 21 overexpressed protein, DS critical region 1 protein, a regulator of calcineurin, modulates axonal outgrowth and brain derived neurotrophic factor-induced growth cone guidance via local protein synthesis and cofilin phosphoregulation (Gehler et al, 2004; Wang W. et al, 2016). Furthermore, DS critical region 1 protein also interacts with Fragile X mental retardation protein, with which it may share a common pathway leading to intellectual disability (Wang et al, 2012).…”
Section: Modulating Cofilin Activity Alleviates Deficits In Rodentmentioning
confidence: 99%
“…Modification of peptide drugs to overcome this is part of the drug design process. Possible modifications include incorporation of D-stereoisomer amino acids (such as in the peptide DAPTA), N-terminal acetylation, C-terminal amidylation, or fusion to a very stable protein such as human serum albumin (Weinstock et al, 2012; Wang et al, 2016). The peptides used in the above studies were i.v.…”
Section: Challenges In Delivery Of Peptide Therapeuticsmentioning
confidence: 99%